How can China prepare for the domestic cultivation of Bt maize?. (March 2018) - Li, Yunhe; Hallerman, Eric M.; Peng, Yufa
Abstract: Recent documents issued by the State Council of China indicate that China's central government is paving the way to commercial cultivation of genetically engineered (GE) staple crops, with priority on insect-resistant GE (IRGE) maize expressing Bacillus thuringiensis ( Bt ) proteins. Multiple Bt maize lines have been developed in China, and their efficacy and benefits to human health and the environment have been demonstrated. We here consider issues regarding approval of GE lines for international trade, measures to be taken to ensure harmonious co-production of GE and non-GE crops, and management of evolution of Bt resistance in maize pests that should be addressed before commercialization of Bt maize in China. Highlights: The prevalence of small-holders presents issues for introduction of Bt maize cultivation. A specialist agency might assist GE crop breeders manage regulatory and trade issues. China should manage co-existence of organic, conventional and GE crops. Alternative strategies for managing insect resistance in Bt maize should be evaluated.